Penafsiran al-Qur’an atas Adopsi Anak: Aplikasi Tafsir Kontekstual Abdullah Saeed Pada QS. al-Ahzâb [33]: 4-5 - Abdullah khoirur Rofiq; Ahmad Farih; Khoirul Umami (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2024)
Child adoption is one way for parents who have not had children for a long time. In the past, adoption became the custom of the pre-Islamic Arabs, they treated their adopted children like their own biological children, even pinning their name behind the name of the adopted child. Islam prohibits the prophet from putting his name behind the name of Zaid ibn Haritsah as in Q.S. al-Ahzâb [33]: 4-5, besides that, the rights of adopted children in the pre-Islamic era were cut off such as getting inheritance and mahram. The research method used is library research by documenting scientific works as research sources and exploring the meaning of the text, Abdullah Saeed's Contextual Interpretation method is used, by paying attention to the hierarchy of values and also the steps of interpretation. From the reading, it is produced that it is permissible to adopt a child, provided that the identity of the adopted child is emphasized, while the problem of mahrams can be obtained by breastfeeding the child, if the adoptive parents are willing to give their property then they can make a will, then the status is a grant, if they do not give a will they get a maximum of 1/3 of the share as explained by KHI (The Compilation of Islamic Law) and the child's adoption can be done if it is urgent, but still emphasizes the status of the child as an adopted child. The above problems can be resolved by entrusting orphans to orphanages.